Lightning Interaction with Power Systems : Fundamentals and Modelling, Volume 1. - Piantini, Alexandre (Institution of Engineering & Technology, 2020)
This book assesses how global lightning may respond to global climate change, provides thorough coverage of the lightning phenomenon and its interaction with various objects, and covers methods for the effective protection of structures and systems.
Keywords: Electric lines.; Electromagnetic fields.; Lightning protection.; Overhead electric lines.; elektronické knihy; electronic books